A Training Sequence-Based Ranging Method for R-Mode of VHF Data Exchange System. (5th May 2022) - Sun, Xiaowen; Hu, Qing; Jiang, Yi
Abstract : The space-time reference provided by GNSS is the basis of the 6G mobile communication integrating land, sea, air, and space. But GNSS has natural vulnerability. In order to solve this problem at sea, ships should be equipped with both space-based and land-based positioning and navigation systems in the future. The Ranging Mode (R-Mode) of the existing maritime communication system is an economical land-based backup positioning system, which is also an important support for e-Navigation. This paper proposes a pseudorange measurement method based on training sequence with multicorrelators, which can be used in the R-Mode of the VHF data exchange system (VDES). This method uses the correlation property of the ASM and VDE training sequence in the VDES for ranging. It reproduces the training sequence in the receiver, and then, noncoherent correlates with the received signal, meanwhile using the pseudorange measurement method with multicorrelators to reduce the influence of pulse shaping on the correlation curve. This paper also gives a design of receiver to implement the proposed method. Experiments are carried out based on the receiver to evaluate the ranging performance. The results show that, compared with the traditional maximum correlation value and E-L methods, the multicorrelator method can effectively reduce the ranging error. When E s / N 0 is greater than 15 dB, the ranging accuracy of the proposed method can be better than 3 m. With the proposed method, the VDES signal can be used for both ranging and communication. Compared with the general VDES function, it does not occupy any additional time slot resources. This provides a reference for the future research of the VDES R-Mode, which can be used to solve the vulnerability problem of the GNSS on maritime communication.